Author correction: Wafer-scale two-dimensional ferromagnetic Fe3GeTe2 thin films grown by molecular beam epitaxy. (December 2017) - Liu, Shanshan; Yuan, Xiang; Zou, Yichao; Sheng, Yu; Huang, Ce; Zhang, Enze; Ling, Jiwei; Liu, Yanwen; Wang, Weiyi; Zhang, Cheng; Zou, Jin; Wang, Kaiyou; et al.
Abstract A correction to this article has been published and is linked from the HTML version of this article.